Retailer licensing and tobacco display compliance: are some retailers more likely to flout regulations?. Issue 2 (8th April 2016) - Fry, Rae; Burton, Suzan; Williams, Kelly; Walsberger, Scott; Tang, Anita; Chapman, Kathy; Egger, Sam
Abstract : Objectives: To assess retailer compliance with a licensing scheme requiring tobacco retailers to list their business details with the government, to examine whether listed retailers are more likely to comply with a point-of-sale (POS) display ban and other in-store retailing laws and to explore variations in compliance between different retailer types and locations. Method: An audit of 1739 retailers in New South Wales, Australia, was used to assess compliance with tobacco retailing legislation. Auditors actively searched for and audited unlisted retailers and all listed retailers in 122 metropolitan and regional postcodes. Multivariate generalised linear regression models were used to examine associations between compliance and retailer type, remoteness and demographic characteristics (socioeconomic level, proportion of population under 18 years and proportion born in Australia). Results: One unlisted tobacco retailer was identified for every 12.6 listed tobacco retailers. Unlisted retailers were significantly more likely than listed retailers to breach in-store retailing laws (p<0.001). Compliance with the POS display ban was observed in 91.3% of tobacco retailers, but compliance with all retailing laws was only 73.4%. Retailers in socioeconomically disadvantaged areas had lower compliance than those in high socioeconomic areas. Conclusions: Some tobacco retailers did not list their business details with the government as required, even though there was no financial cost to do so. Unlisted retailers were more likely to violate in-store regulations. The results suggest licensing schemes can be useful for providing a list of retailers, thus facilitating enforcement, but require a system to search for, and respond to, unlisted/unlicensed retailers.